Основні показники та вимоги до захватних пристроїв промислових роботів - Павленко, І. І.; Годунко, М. О.; Кропівний, В. М.; Pavlenko, I.; Godunko, M.; Kropivniy, V. (КНТУ, 2012)
Проаналізовано технічні характеристики захватів роботів та показники їх якості. Також розглянуто вимоги до захватів загального характеру і спеціального призначення, пов'язані з конкретними умовами їх роботи. Надано рекомендації щодо вибору вимог до проектування захватних пристроїв. The row of basic indexes and requirements is offered to grippers of industrial robots. Technical descriptions are analysed on the groups of grippers of robots and row their general indexes. Additional requirements are also considered to grippers of general character and special, which related to the concrete terms of their work. It is offered to recommendation on the choice of terms and requirements of planning of grippers.
Basic indexes and requirement to grippers of industrial robots
Keywords: промисловий робот; захватний пристрій; експлуатаційні показники; вимоги до захватних пристроїв